Traffickers and Victims: Opposite sides of the same coin? - Helen Leung; Crystal Yeung; Patricia Ho (Anti-Trafficking Review, 2022)
Hong Kong Dignity Institute (HKDI) provides direct assistance to victims of trafficking and seeks to break cycles of exploitation through institutional change. Drawing from first-hand testimonials of over 30 individuals we have assisted since 2019 and insight from our civil society partners, in this article, we outline our observations of traffickers and their modus operandi in three prevalent trafficking scenarios in Hong Kong. Our experience suggests that trafficking networks are composed of a complex and fluid interplay of actors with blurred emotional lines between the traffickers and victims. We conclude that anti-trafficking efforts in Hong Kong are hampered by difficulties in identifying traffickers given the elusive nature of their activities.